Brightening effect of Ziziphus jujuba (jujube) fruit extract on facial skin: A randomized, double‐blind, clinical study. Issue 7 (30th April 2022) - Aafi, Ensiye; Shams Ardakani, Mohammad Reza; Ahmad Nasrollahi, Saman; Mirabzadeh Ardakani, Mehran; Samadi, Aniseh; Hajimahmoodi, Mannan; Naeimifar, Atefeh; Pourjabbar, Zeinab; Amiri, Fateme; Firooz, Alireza
Abstract: Ziziphus jujuba Mill. (jujube) is an invaluable medicinal plant in traditional and modern medicine. Jujube syrup is a complex of herbal extracts including Z. jujuba, Berberis vulgaris, Rhus coriaria, Prunus domestica, and Rosa damascene . The purpose of the present study was to formulate and investigate the efficacy and safety of jujube syrup on brightening of facial skin. In this randomized, double‐blind, controlled clinical study, 46 participants consumed jujube syrup or placebo (23 in each group) twice a day for 8 weeks. The number of pigments, area of pigmentation, and physician's global assessment score (PGAS) were evaluated at baseline and after 8 weeks. The results showed the amounts of total phenolics and flavonoids were 81.97 ± 0.25 and 4.98 ± 1.04 mg/ml, respectively. The amounts of organic acids (gallic acid and chlorogenic acid) were quantified at 1140 ± 17.65 and 1520 ± 25.77 μg/ml, respectively. The amounts of total phenolic and flavonoids were stable under accelerated conditions. Eight weeks after treatment, the number of pigment counts reduced to 0.545 ± 0.307 compared to the placebo group. Moreover, the pigmented area and its percentages were significantly reduced to 0.556 ± 0.285 and 0.561 ± 0.288 in jujube syrup compared with placebo, respectively. Jujube syrup is efficient and safe for treating hyperpigmentation of the face.